Perubahan Gaya Dakwah Da’i di Bulan Ramadhan dalam Pandemi Covid 19 (Perspektif Psikologi Da’i) - Zidni Ilman Nafia; Khafidhoh Khafidhoh (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah, Institut Agama Islam Sunan Giri Ponorogo, 2021)
In the midst of the outbreak of the Covid 19 (Corona Virus) pandemic which has killed thousands of people in the world, it is a very frightening thing for most people, until the government implements regional closures, PSBB (large-scale social restrictions), and quarantine of such areas to stop the spread of this Corona Virus . However, in the middle of the holy month of Ramadan, preaching activities are increasingly being carried out because this month Muslims want to flock to improve themselves and increase their charity. Islam and da'wah are two inseparable things. Islam will not progress and develop bersyi'ar and shine without any efforts to preach. The more incessant preaching efforts are carried out, the more Islamic religion is shouting, the more lax the efforts of preaching the fainter the light of Islam in society. Latsaal-islam illa bi al-da'ah, that's a wise word expressed in the book of kyai prostitution. In facing the era of globalization of information and technological developments lately, the world is faced with the rapid development of information flows. It seems that the use of technology tools as a medium for conveying information to the public cannot be stopped. But on the contrary, the existence of sophisticated technology in the era of globalization of information and communication can be used for disseminating information and messages of Islamic da'wah. In relation to the psychology of da'i, da'i can do what he wants to do because of a change in social society. The psychology of a good da'i will be able to provide a good da'wah effect in society.